2020
DOI: 10.1177/1091581820945985
|View full text |Cite
|
Sign up to set email alerts
|

Novel Toxicology Program to Support the Development of Inhaled VentaProst

Abstract: Currently, off-label continuous administration of inhaled epoprostenol is used to manage hemodynamics during mitral valve surgery. A toxicology program was developed to support the use of inhaled epoprostenol during mechanical ventilation as well as pre- and postsurgery via nasal prongs. To support use in patients using nasal prongs, a Good Laboratory Practice (GLP), 14-day rat, nose-only inhalation study was performed. No adverse findings were observed at ∼50× the dose rate received by patient during off-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…iEPO has been reported to produce mild acute sterile tracheitis in animal models. However, a recent novel toxicology program showed no drug-related airway or lung inflammation [16].…”
Section: Inhaled Pgi2mentioning
confidence: 99%
“…iEPO has been reported to produce mild acute sterile tracheitis in animal models. However, a recent novel toxicology program showed no drug-related airway or lung inflammation [16].…”
Section: Inhaled Pgi2mentioning
confidence: 99%
“…More studies are needed to determine the role. Inhaled epoprostenol has been reported that it can produce mild acute sterile tracheitis in animal model, however, recent novel toxicology program showed no drug related airway or lung inflammation (157,158).…”
Section: Epoprostenolmentioning
confidence: 99%